Albanskij toskskij govor sela Lešnja (Leshnja) - kraina Skrapar. Sintaksis, Leksika, Etnolingvistika, Teksty - Ylly, Xhelal; Sobolev, Andrej N. (Bern Peter Lang International Academic Publishing Group, 2002)
Slavic languages
German
Keywords: Language teaching & learning (other than ELT); Slavic languages